2020
DOI: 10.1186/s12933-020-01191-5
|View full text |Cite
|
Sign up to set email alerts
|

How should we monitor the cardiovascular benefit of sodium–glucose cotransporter 2 inhibition?

Abstract: Sodium–glucose cotransporter 2 (SGLT2) inhibitors are increasingly prescribed for the treatment of patients with type 2 diabetes to reduce the risk of cardiovascular events, including heart failure (HF). The mechanisms by which SGLT2 inhibitors reduce such risk are likely to be independent of diabetes status and improvement of glycemic control. In this commentary, based on recent mediation analyses of cardiovascular outcome trials with SGLT2 inhibitors, we discuss the prognostic role of a well-known HF-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, a recent mediation analysis in the Canagliflozin Cardiovascular Assessment Study (CANVAS) program reported that the decrease in NT-proBNP concentration caused by treatment with a SGLT2 inhibitor was associated with a relatively small reduction in the risk of HF-related events [ 34 ]. Therefore, there is an urgent need to establish reliable markers for predicting or monitoring the cardiovascular benefits of SGLT2 inhibitors [ 35 ]. In this regard, changes in some fluid volume parameters indicative of a hemodynamic effect of SGLT2 inhibition are likely to be associated with clinical benefits [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent mediation analysis in the Canagliflozin Cardiovascular Assessment Study (CANVAS) program reported that the decrease in NT-proBNP concentration caused by treatment with a SGLT2 inhibitor was associated with a relatively small reduction in the risk of HF-related events [ 34 ]. Therefore, there is an urgent need to establish reliable markers for predicting or monitoring the cardiovascular benefits of SGLT2 inhibitors [ 35 ]. In this regard, changes in some fluid volume parameters indicative of a hemodynamic effect of SGLT2 inhibition are likely to be associated with clinical benefits [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SGLT2 inhibitors have been used to treat patients with T2DM to reduce the risk of CV events, including HF, and it is clear that the mechanism by which SGLT2 inhibitors reduce this risk may not be directly related to improved diabetic status and glycemic control. In addition, short-term use of SGLT2 inhibitors significantly improved volume load and symptoms in HF patients with concomitant T2DM; however, serum N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentrations, which are traditionally used to assess HF severity, did not improve significantly, suggesting that we need to explore meaningful biomarkers that can monitor and evaluate the effect SGLT2 inhibitors for HF treatment in the future ( 55 ), in order to provide scientific evidence for in-depth understanding of the many unknowns of SGLT2 inhibitors.…”
Section: Perspectivementioning
confidence: 99%
“…Thus, the reduction of adverse cardiovascular outcomes suggests that SGLT2i may have plausible class effects on cardiorenal outcomes. Therefore, several theories of the mechanism of action of SGLT2i in heart failure have been postulated [11,12]. First, SGLT-2i could affect cardiovascular risk factors, such as improving the metabolic profile; reducing plasma glucose levels, blood pressure, and body weight; and modifying the lipid profile.…”
Section: Introductionmentioning
confidence: 99%